2001
DOI: 10.1016/s0886-3350(00)00858-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophakic ametropia managed with a phakic posterior chamber intraocular lens

Abstract: We report the use of a phakic posterior chamber intraocular lens (IOL) to correct pseudophakic ametropia. Two eyes of 2 patients developed ametropia after unilateral phacoemulsification and IOL implantation. The manifest refraction was -6.00 -0.50 x 50 in the first patient and +4.50 -1.00 x 15 in the second. Both patients were bothered by the induced anisometropia and had posterior chamber phakic IOL implantation in the pseudophakic eye. Postoperatively, uncorrected visual acuity improved from 20/400 to 20/30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“… 6 Supplementary IOL implantation using ICLs have been reported with satisfactory results. 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“… 6 Supplementary IOL implantation using ICLs have been reported with satisfactory results. 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…The first reported use of pIOLs in pseudophakic eyes was performed by Kojima et al [ 13 ] in 2010, who showed in 8 pseudophakic eyes of 5 patients who underwent piggyback insertion of a pIOL to correct residual refractive error that pIOL placement in this situation was effective with predictable results. In a subsequent study by Hsuan et al [ 14 ] of 6 pseudophakic patients with anisometropia who received pIOLs, anisometropia was decreased to asymptomatic levels, with a mean decrease in anisometropia of 3.15 D. Another case was described of an 80-year-old female with pseudophakic ametropia who received a pIOL with marked improvement in visual acuity and elimination of anisometropia [ 15 ]. In 14 pediatric eyes with pseudophakic myopic anisometropic amblyopia, Eissa [ 16 ] described improved visual acuity and a decrease in manifest refraction spherical equivalent from −5.23 to −0.30 D with implantation of pIOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatively, there were risks of intraocular pressure increase, IOL shift and pupil capture [ 12 14 ]. ICL compare favorably with IOL as the enough vault between the ICL and the primary IOL may contribute to decreasing the opacity [ 15 – 18 ]. Also, Toric ICL can correct the astigmatism.…”
Section: Discussionmentioning
confidence: 99%